Computational Linguistics and Intelligent Text Processing : 8th International Conference, CICLing 2007, Mexico City, Mexico, February 18-24, 2007 : proceedings - Gelbukh, Alexander (Springer, 2007)
This book constitutes the refereed proceedings of the 8th International Conference on Computational Linguistics and Intelligent Text Processing, CICLing 2007, held in Mexico City, Mexico in February 2007. The 53 revised full papers presented together with 3 invited papers were carefully reviewed and selected from 179 submissions. The papers cover all current issues in computational linguistics research and present intelligent text processing applications. The papers are organized in topical sections on: lexical resources, corpus-based knowledge acquisition, morphology and part-of-speech tagging, named entity recognition, temporal expression treatment, word segmentation, sentence splitting, chunking, grammar formalisms and syntax, word sense disambiguation and discrimination, semantics, humor and emotion analysis; machine translation, natural language generation, intelligent tutoring systems, information retrieval, question answering, text summarization and information extraction, text categorization and clustering, and spell-checking.